Miura and generalized Bï¿½cklund transformation for KdV hierarchy - Gomes, J. F. [UNESP]; Retore, A. L. [UNESP]; Zimerman, A. H. [UNESP] (IOP Publishing, 2016)
Using the fact that Miura transformation can be expressed in the form of gauge transformation connecting the KdV and mKdV equations, we discuss the derivation of the Bï¿½cklund transformation and its Miura-gauge transformation connecting both hierarchies.
Keywords: Bcklund transformation; integrable models; solitons